Production of Al/Al2O3p Metal Matrix Composites (MMC) by Semisolid metal processing method - H., Budiman; Mohd. Zaidi, Omar; Azman, Jalar (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.